Risk Factors for Anorectal Dysfunction After Interspincteric Resection in Patients With Low Rectal Cancer - Min, Li; Fan, Zhang; Zhi, Wang; Pingang, Li; Lijuan, Xie; Min, Deng; Yan, Wen; Xiaosong, Wang; Bo, Tang (Frontiers in Surgery, 2021)
Purpose: To explore the risk factors for anorectal dysfunction after intersphincteric resection in patients with low rectal cancer. Methods: A total of 251 patients who underwent intersphincteric resection from July 2014 to June 2020 were included in this study, for which the Kirwan’s grade, Wexner score and anorectal manometric index were used to evaluate the anorectal function and the parameters including demographics, surgical features, and clinical and pathological characteristics were analysed to explore the potential risk factors for anorectal function after intersphincteric resection. Results: In the 251 included patients, 98 patients underwent partial intersphincteric resection, 87 patients underwent subtotal intersphincteric resection and 66 patients underwent total intersphincteric resection. Fifty-three (21.1%) patients had postoperative complications while no significant difference was observed between the three groups. Thirty patients (45.5%) in the total intersphincteric resection group were classified as having anorectal dysfunction (Kirwan’s grade 3-5), which was significantly higher than that in the partial intersphincteric resection group (27.6%) and subtotal intersphincteric resection group(29.9%). The mean Wexner score of total intersphincteric resection patients was 7.9, which was higher than that of partial intersphincteric resection patients(5.9, p=0.002) and subtotal intersphincteric resection patients(6.4, p=0.027). The initial perceived volume was lower in the total intersphincteric resection group than in the partial and subtotal intersphincteric resection groups at 1, 3, and 6 months after intersphincteric resection, and the resting pressure, maximum squeeze pressure and maximum tolerated volume in the total intersphincteric resection group were worse than those in the partial and subtotal groups at 3 and 6 months after intersphincteric resection. Univariate and multivariate analyses suggested that age ≥ 65, total intersphincteric resection and preoperative chemoradiotherapy were independent risk factors for anorectal dysfunction(P = 0.023, 0.003 and 0.008 respectively). Of the 66 patients who underwent total intersphincteric resection, 17 patients received preoperative chemoradiotherapy, of which 12 patients(70.6%) were classified as having anorectal dysfunction. Conclusion: Age ≥ 65, total intersphincteric resection and preoperative chemoradiotherapy were risk factors for anorectal dysfunction after intersphincteric resection. The morbidity of anorectal dysfunction after total intersphincteric resection for patients who received preoperative chemoradiotherapy was relatively high, and the indication should be carefully evaluated.